"Am I Even Going to Be Well-Liked in Person?": First-Year Students' Social Media Use, Sense of Belonging, and Mental Health. Issue 3 (3rd July 2022) - Stebleton, Michael J.; Kaler, Lisa S.; Potts, Charlie
Abstract: Evidence suggests that rising mental health concerns represent a critical issue in higher education. This issue takes on particular importance among first-year students as they transition to college and attempt to form meaningful relationships with their new peers. Social media interaction now represents a primary means of communication for students, and researchers must understand the effects of social media on college students' sense of belonging, identity, and mental health. This study explores the intersection of social media use, mental health, and sense of belonging among first-year students at a large, public university. Using a Giorgian phenomenological approach, we analyzed 26 qualitative interviews with first-year students during their first semester of college. Three main themes are explored: seeking belonging through in-person interactions; seeking belonging through social media use; and experiencing negative mental health impacts of social media. Findings illuminate the role of social media in the transition to college and the potential impacts on sense of belonging and mental health. Implications for practice, policy, and research are discussed.